The Impact of Tourism Villages Regulations to Achieve Sustainable Villages Tourism - Abdul Kadir Jaelani; Dinda Aprilia; Bobur Sobirov; Erkinboy Rakhimovich Abdullaev (Contrarius, 2025)
Tourism constitutes a concurrent governmental function in Indonesia, whereby regional governments are vested with the authority to regulate and manage tourism development, including the governance of tourist villages. Despite the incorporation of sustainable tourism principles into national legislation as a means of supporting the Sustainable Development Goals (SDGs), particularly through the integration of economic, environmental, social, and cultural considerations, legal scholarship remains limited in critically examining the effectiveness of their implementation at the regional level. This gap is especially evident in the context of forest-based tourist villages. This study aims to examine the implementation of sustainable tourism principles as stipulated in national legislation in the management of tourist villages located within forest areas of Karanganyar Regency and to analyze the implications of such implementation for social, economic, cultural, and environmental dimensions. This research employs a normative legal research method, focusing on the analysis of statutory regulations, legal doctrines, and relevant policy instruments, and adopts a prescriptive analytical approach. The findings demonstrate, first, that the existing normative framework governing sustainable tourist village management has contributed to local economic development and is aligned with Sustainable Development Goal (SDG) 8 concerning decent work and economic growth. Second, the study finds that significant deficiencies persist in practical implementation, particularly with regard to environmental management and the enforcement of tourism regulations. Third, these deficiencies indicate a structural disparity between normative legal objectives and their realization in practice, reflecting weaknesses in regional governance and institutional coordination. The study concludes that regulatory refinement and strengthened governance mechanisms are necessary to ensure legally consistent, environmentally sustainable, and socially inclusive tourist village management in forest areas.